Passing Practice Using Targets to Improve the Results of Futsal Game Passing Accuracy in Extracurricular Elementry Labschool UMJ - Ghani, M Al; Yulianingsih, Ika; Mulyana, Irham Hudaya (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
This research is based on problems that occur in extracurricular futsal at Elementry of Labschool UMJ, where the results of passing accuracy are considered not maximal. From these problems, researchers tried to offer solutions for passing accuracy training by using targets as a reference in increasing passing accuracy. This research uses one group pretsest-postest experimental research method. The population in this study was 30 people. The sample in this study was 30 people with total sampling techniques. From the calculation results that have been tested, the pre-test results show the effect of target passing training on passing accuracy getting a value of 46.67. The average post-test result was 56.33, an increase between pretest and post-test of 8.66. Based on the results of the normality test, the Passing pre-test using the target gets a result of 0.186 and the post-test Passing group using the target has a statistical significance of 0.219. With the SPSS 25 program, all these data of 0.186, 0.219 and 0.265 > 0.05 meet the tolerance limit of the Kolmogrov-Smirnov normality test at a significance level of 5%. Based on the results of the homogeneity test, pre-test and post-test passing data using targets and also improvement data for passing exercises using targets with significant levels are 0.699, 0.699, 0941 > 0.05 > 0.05. Based on the data from the pre-test and post-test passing results using the targets presented in the t test results, a t value of -3.058 and statistical significance of 0.0001 was obtained. There is an effect of passing training using targets on accuracy with t count - 3.058 < -t table -6.117 and significant values 0.001< 0.05.